A Survey on Emergence of Cloud Computing Using Brokering Services - Mahesh kumar, B; Savitha, V (International Journal of Computer Sciences and Engineering, 2025)
Trust management is very crucial aspect in multiple cloud environment .To ensure this Trust-management. Our paper presents C-provider, a trust aware brokering scheme for managing efficient cloud resources (or) services. The C-provider is based on a third party brokering architecture that is proposed to act as a middleware for cloud management and service matching.Our C-provider uses a hybrid and adaptive trust model to compute the overalltrust degree of resources based on the monitored feedbackof the service resources. Also C-provider uses a minimal feedback mechanism that effectively reduces networking issue and improve system efficiency.